Astaxanthin-loaded polylactic acid-glycolic acid nanoparticles ameliorate ulcerative colitis through antioxidant effects - Li, Chunmei; Zhou, Yu; Yuan, Meng; Yang, Yawen; Song, Ruilong; Xu, Gang; Chen, Gang (Frontiers in Nutrition, 2023)
Astaxanthin (AST) is a kind of carotenoid with vigorous antioxidant activity. However, the development and utilization of AST are limited by aqueous insolubility and low bioavailability. This study is designed to investigate whether AST@PLGA could inhibit UC and reveal its potential mechanism. In this study, AST-loaded polylactic acid-glycolic acid (AST@PLGA) nanoparticles were prepared by the emulsion solvent evaporation method. The particle size, polydispersity index, and zeta potential of AST@PLGA were 66.78±0.64 nm, 0.247, and -9.8±0.53 mV, respectively, and were stable within 14 days. In addition, the antioxidant activities of AST and AST@PLGA in vitro were evaluated. It was observed that the AST@PLGA nanoparticles not only maintained the effect of AST but also had a sustained-release effect. Subsequently, the mouse model of acute colitis was established to determine the protective effects of AST@PLGA. Experiments on mice indicated that AST@PLGA effectively reduced the levels of MDA, TNF-α, IL-1β, and IL-6, and increased the level of SOD. AST@PLGA also down-regulated the protein expression of P38 and ERK. The results exhibited the positive protective effect of AST@PLGA in inhibiting acute colitis. Based on the above, AST@PLGA nanoparticles have good stability and ameliorative effects on colitis, which could be functional foods in the future.